Patient preferences for HIV/AIDS therapy: A discrete choice experiment - Axel C. Mühlbacher; Matthias Stoll; Jörg Mahlich; Matthias Nübling (Health Economics Review, 2013)
Objectives: An increasing emphasis on patient-centred health care and shared decision making requires an intensive consideration of patient preferences. In the present study, patient preferences regarding treatment of HIV/AIDS were explored using direct assessment and discrete choice experiment (DCE). Methods: Based on literature research about preferences of HIV/AIDS patients we conducted a qualitative pre-study. The results were used to compose a questionnaire on relevant aspects of HIV/AIDS treatment which underwent a pre-test. In the subsequent quantitative study phase presented here, the following data were collected online or on paper including socio-demographic data, SF12v2, data on HIV/AIDS, antiretroviral treatment and patient preferences for therapy characteristics using direct measurement, as well as a discrete choice experiment. Results: 218 patients completed the quantitative main study, 82% of these on paper. 86% were male and the most frequent age group was between 45 and 54years (37.6%). The SF12v2 showed a mean value of 43 points for the 'mental health' component sum score. In the direct measurement the most relevant therapy characteristics were 'Self-application of the drug (at home or on-the-go) possible', 'Drug has very high efficacy (reduction of viral load)' and 'Long term (hidden) damage (e.g. organ damage) is unlikely'. Based on a factor analysis, six treatment characteristics were selected and used to generate eight virtual therapies. To evaluate the patient assessments a random effect logit model was employed. All of the characteristics were statistically significant predictors of the model of patient preference. The most important therapy characteristic was that the disease is not obvious for others. Conclusions: The main result is the high impact of quality of life, in particular the emotional quality of life on patient preferences on the selection of treatments. Thus, the selection of particular treatment options should be accompanied by a deliberate consideration of treatment features, which need to be considered in order to maximize patient adherence and compliance.
Keywords: 330